2000
DOI: 10.1017/s1368980000000392
|View full text |Cite
|
Sign up to set email alerts
|

Socioenvironmental influences on children's fruit, juice and vegetable consumption as reported by parents: reliability and validity of measures

Abstract: Objective: To pilot test theory-based questionnaires to measure socioenvironmental in¯uences on children's fruit, juice and vegetable (FJV) consumption as reported by parents. Design: Cross-sectional. Setting: Parents of fourth to sixth grade students completed socioenvironmental questionnaires. The students completed food records (FRs) for 2 days in the classroom. Subjects: Interviews were completed by 109 parents (17% African-American, 32% Hispanic-American and 51 Euro-American). Results: Student mean daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
111
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(120 citation statements)
references
References 38 publications
(49 reference statements)
7
111
1
1
Order By: Relevance
“…The latter has also been found in previous studies of 11-12-year-olds (16) and 4th-6th graders (23) .…”
Section: Discussionsupporting
confidence: 87%
“…The latter has also been found in previous studies of 11-12-year-olds (16) and 4th-6th graders (23) .…”
Section: Discussionsupporting
confidence: 87%
“…Children like to consume products they know -the more often children eat a given product, the more they like it. Children familiarize themselves with new tastes and products through experience as well as by observing dietary behaviours of other people present in their environment (parents, siblings, peers) (4,31,34,35) . The present study confirmed the role of the influence exerted by the family environment and health-oriented attitudes of parents (parents eating F&V, encouraging children to eat F&V, giving sliced F&V between meals, giving children F&V to take to school) on the F&V consumption of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have developed measures of the availability and accessibility of healthy and less healthy foods in the home with most emphasis placed on fruits and vegetables (18,36,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)54,55,57,59,(61)(62)(63)65) . While no gold standard exists for examining availability and accessibility of foods, some trials have used in-home inventories.…”
Section: Food Availability and Accessibilitymentioning
confidence: 99%
“…Despite the validity of in-home inventories conducted by researchers, it is often not feasible to conduct this type of resource-intensive assessment and a checklist format completed by participants may be more practical. Many of the checklists focus on availability and accessibility of fruit and vegetables (11,(40)(41)(42)(43)(44)(45) , and some on less healthful foods (18) , while others include a full range of food groups to reflect the typical US diet (46) . Availability has also been assessed most basically by asking whether caregivers purchase foods on their child's request and if foods are visible (47) .…”
Section: Food Availability and Accessibilitymentioning
confidence: 99%